The thermodynamic landscape of methanogenic PAH degradation - Dolfing, Jan (Blackwell Publishing Ltd, 2009)
Methanogenic degradation of polycyclic aromatic hydrocarbons (PAHs) has long been considered impossible, but evidence in contaminated near surface environments and biodegrading petroleum reservoirs suggests that this is not necessarily the case. To evaluate the thermodynamic constraints on methanogenic PAH degradation we have estimated the Gibbs free energy values for naphthalene, phenanthrene, anthracene, pyrene and chrysene in the aqueous phase, and used these values to evaluate several possible routes whereby PAHs may be converted to methane. Under standard conditions (25°C, solutes at 1 M concentrations, and gases at 1 atm), methanogenic degradation of these PAHs yields between 209 and 331 kJ mol(−1). Per mole of methane produced this is 27–35 kJ mol(−1), indicating that PAH‐based methanogenesis is exergonic. We evaluated the energetics of three potential PAH degradation routes: oxidation to H(2)/CO(2), complete conversion to acetate, or incomplete oxidation to H(2) plus acetate. Depending on the in situ conditions the energetically most favourable pathway for the PAH‐degrading organisms is oxidation to H(2)/CO(2) or conversion into acetate. These are not necessarily the pathways that prevail in the environment. This may be because the kinetic theory of optimal length of metabolic pathways suggests that PAH degraders may have evolved towards incomplete oxidation to acetate plus H(2) as the optimal pathway.